Ca2+ alterations in familial Alzheimer's disease (FAD) - Pizzo, Paola (Henry Stewart Talks, 2007)
Introduction to Alzheimer's disease, Morphological and functional features, Genetic studies, Presenilin functions and calcium homeostasis, Calcium dyshomeostasis and FAD, Modulatory role of presenilin on IP3-evoked Calcium release, Different effects of PS mutants on intracellular Calcium stores, A reformulation of the 'Calcium hypothesis' for FAD
Updated at 2011/07/27